Autistic Traits Are Associated With Decreased Activity of Fast Sleep Spindles During Adolescence - Merikanto, Ilona (J Clin Sleep Med, 2019)
STUDY OBJECTIVES: Autistic traits present a continuum from mild symptoms to severe disorder and have been associated with a high prevalence of sleep problems. Sleep spindles have a key function in sleep maintenance and in brain plasticity. Previous studies have found decreased spindle activity in clinical autism. Here we examine the associations between the entire range of autistic traits and sleep spindle activity in a nonclinical community cohort of adolescents. METHODS: Our cohort is based on 172 adolescents born in 1998 (58.7% girls, mean age = 16.9 years, standard deviation = 0.1), who filled in the adult autism-spectrum quotient (AQ), consisting of total score, and social interaction and attention to details subscales. Participants underwent an ambulatory overnight sleep electroencephalography. Sleep spindles (amplitude, duration, density, and intensity) were automatically detected from stage N2 sleep, and divided to slow and fast spindles. RESULTS: Higher AQ total sum and social interaction sum associated with lower fast spindle amplitude and intensity (P < .04). No associations were observed for attention to details. CONCLUSIONS: Our findings indicate that a higher level of autistic traits in the nonclinical range among generally healthy adolescents associate with similar alterations in sleep spindle activity as observed in many neuropsychiatric conditions, indicating lower sleep-related brain plasticity. This indicates that sleep microstructures form a continuum that follows self-reported symptoms of autism. CITATION: Merikanto I, Kuula L, Makkonen T, Salmela L, Räikkönen K, Pesonen AK. Autistic traits are associated with decreased activity of fast sleep spindles during adolescence. J Clin Sleep Med. 2019;15(3):401–407.